Awareness and intention-to-use of digital health applications, artificial intelligence and blockchain technology in breast cancer care - Griewing, Sebastian; Knitza, Johannes; Gremke, Niklas; Wallwiener, Markus; Wagner, Uwe; Lingenfelder, Michael; Kuhn, Sebastian (Frontiers in Medicine, 2024)
Emerging digital technologies promise to improve breast cancer care, however lack of awareness among clinicians often prevents timely adoption. This study aims to investigate current awareness and intention-to-use of three technologies among breast cancer healthcare professionals (HCP): (1) digital health applications (DHA), (2) artificial intelligence (AI) and (3) blockchain technology (BC). A 22item questionnaire was designed and administered before and after a 30-minute educational presentation highlighting technology implementation examples. Technology awareness and intentionto-use were measured using 7-point Likert scales. Correlations between demographics, technology awareness, intention-to-use, and eHealth literacy (GR-eHEALS scale) were analyzed. 45 HCP completed the questionnaire, of whom 26 (57.8%) were female. Age ranged from 24 to 67 {mean age (SD): 44.93 ±12.62}. Awareness was highest for DHA (68.9%) followed by AI (66.7%) and BC (24.4%). The presentation led to a non-significant increase of intention-to-use AI {5.37 (±1.81) to 5.83 (±1.64)}. HCPs´ intention-to-use BC after the presentation increased significantly {4.30 (±2.04) to 5.90 (±1.67), p<0.01}. Mean accumulated score for GR-eHEALS averaged 33.04 (± 6.61). HCPs´ intended use of AI significantly correlated with eHealth literacy (ρ = 0.383; p<0.01), intention-to-use BC (ρ = 0.591; p<0.01) and participants´ age (ρ = -0.438; p<0.01). This study demonstrates the effect that even a short practical presentation can have on HCPs´ intention-to-use emerging digital technologies. Training potential professional users should be addressed alongside the development of new information technologies and is crucial to increase HCPs´ corresponding awareness and intended use.